Knowledge and Practice Regarding Menstrual Hygiene among School Going Adolescents of Kohalpur Municipality - Mahato, Lalan; Poudel, Priyanka; Jaishwal, Aakash; Pathak, Sheetal (International Journal of Silkroad Institute of Research and Training, 2023)
Background: Menstruation is still considered as stigma in our society. The talks and discussion regarding menstruation is not quite acceptable because of shame   and fear. Therefore many girls and women have become the victim of sour incidents like diseases ,rape ,death ,depression etc. We made a small effort to access knowledge and practice regarding menstrual hygiene among school going adolescent girls of Kohalpur municipality through study.Method: A cross sectional study was conducted from June to September 2021 among 359 students from grade eight, nine and  ten of 4 different schools of  Kohalpur municipality. Semiopen questionnaire were prepared and analysis was done to access knowledge and practice regarding menstrual hygiene. Results: 90.3% females had adequate knowledge about menstrual hygiene while 9.75 % females had poor knowledge .Majority of  females were engaged in good menstrual practices.Conclusions: Majority of females had adequate  knowledge about menstrual hygiene but it has not being adequately brought into practices and the attitude of females towards menstrual hygiene is still unsatisfactory. As a result there is a need of awareness programs regarding menstrual hygiene and its management.